Reconsidering the Use of Population Health Surveys for Monitoring of Mental Health - Jorge Arias de la Torre; Gemma Vilagut; Amy Ronaldson; Ioannis Bakolis; Alex Dregan; Fernando Navarro-Mateu; Katherine Pérez; Anna Szücs; Xavier Bartoll-Roca; Antonio J Molina; Matilde Elices; Víctor Pérez-Solá; et al. (JMIR Publications, 2023)
Monitoring of the mental health status of the population and assessment of its determinants are 2 of the most relevant pillars of public mental health, and data from population health surveys could be instrumental to support them. Although these surveys could be an important and suitable resource for these purposes, due to different limitations and challenges, they are often relegated to the background behind other data sources, such as electronic health records. These limitations and challenges include those related to measurement properties and cross-cultural validity of the tools used for the assessment of mental disorders, their degree of representativeness, and possible difficulties in the linkage with other data sources. Successfully addressing these limitations could significantly increase the potential of health surveys in the monitoring of mental disorders and ultimately maximize the impact of the relevant policies to reduce their burden at the population level. The widespread use of data from population health surveys, ideally linked to electronic health records data, would enhance the quality of the information available for research, public mental health decision-making, and ultimately addressing the growing burden of mental disorders.